2003
DOI: 10.1177/001440290307000105
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Analysis of Shifting Policy Landscapes in Special and General Education Reform

Abstract: O ver a 10-year period, three separate, but related, statelevel policy initiatives were implemented in Vermont in an effort to reform special and general education through improving student performance and increasing the capacity of general education to support students in general education classrooms to the greatest extent possible. The first of these, known as Act 230, was designed to increase the capacity of general education teachers to serve students with disabilities and those at risk of academic failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Previous work on the sustainability of both classroom specific and schoolwide reforms (Huberman & Miles, 1984;Klingner et al, 2001) emphasized the importance of the match between a reform and the policy context in which it is implemented. Furney et al (2003) concluded that high-stakes assessment was a poor policy context for classroom-specific reforms; our findings suggest that high-stakes assessment also proved to be a poor context for inclusion, a schoolwide reform. The third principal began at SMS a year before school grades were first awarded, as pressure to perform was being ratcheted up.…”
Section: Change I N State a N D District Policymentioning
confidence: 58%
“…Previous work on the sustainability of both classroom specific and schoolwide reforms (Huberman & Miles, 1984;Klingner et al, 2001) emphasized the importance of the match between a reform and the policy context in which it is implemented. Furney et al (2003) concluded that high-stakes assessment was a poor policy context for classroom-specific reforms; our findings suggest that high-stakes assessment also proved to be a poor context for inclusion, a schoolwide reform. The third principal began at SMS a year before school grades were first awarded, as pressure to perform was being ratcheted up.…”
Section: Change I N State a N D District Policymentioning
confidence: 58%
“…Evidence regarding the extent to which students with LD are being educated in inclusive settings provides critical information regarding how well the mandates from IDEA (e.g., LRE and access to the general education curriculum) are being implemented. Indeed, if these mandates result in little change in placement practices across states, it may be necessary to examine how policies might be altered to more effectively ensure that these mandates are successfully implemented (Furney, Hasazi, Clark/Keefe, & Hartnett, 2003;Roach et al, 2002). For example, Roach et al (2002) and the Consortium on Inclusive Schooling Practices (1996) suggested that systematically examining current state and local district policies can help shed light on placement practices.…”
mentioning
confidence: 99%
“…Conversely, the silos tend to disconnect most students who receive specialized supports under the IDEA from the general curriculum (Lombardi, 1999;Sailor, Doolittle, Bradley, & Danielson, 2009). Moreover, these students often receive instruction from teachers who, though qualified in special education methods, have little or no up-to-date contact with general education curriculum content (Brownell, Ross, Colón, & McCallum, 2005;Furney, Hasazi, Clark-Keefe, & Hartnett, 2003;McLeskey & Billingsley, 2008), but are still expected to participate in annual state assessments aligned to it. Indeed, some research attributes, at least in part, low performance in schools to education silos (Duncombe & Yinger, 2007;Timar & Roza, 2010).…”
Section: Fragmented Systems and Supportsmentioning
confidence: 99%